Smartphone addiction among young adolescents: Integration of flow theory and fear of missing out - Muhammad Ashraf, Fauzi; Siti Aminah, Harun; Tulasi, Martin; Norazha, Paiman; Mohamed Saiful Firdaus, Hussin (Tamkang University, Taiwan, 2021)
In the age of terabytes and milliseconds, a pathological use of smartphone is now growing tremendously among adolescents worldwide. This global phenomenon has made smartphone addiction the most popular type of technology addiction. Underpinned by Flow Theory, this study contributes to the body of knowledge on the consumer behaviour towards a psychological perspective on smartphone usage among students in a Malaysian university. A total of 210 students participated in this study. A partial least square structural equation modelling (PLS-SEM) method was applied in testing the hypotheses. The results show that all nine hypotheses tested on antecedents of smartphone addiction were found to be significant. The strongest predictor discovered in the model is concentration, suggesting that users who are addicted spend countless time in using smartphone due to enormous concentration on entertainment and social networking sites that are commonly available in smartphone applications.